Analysis of Risk Factors for Infant Diaper Dermatitis - Khairina, Fadilah Oliv; Jusuf, Nelva Karmila (Talenta Publisher, 2020)
Infants have skin that is easy to get irritated and infected by microorganisms. The use of diapers in infants often causes diaper dermatitis and disturbs the comfort. The diaper dermatitis incidence is quite high in infants aged 0-24 months. This study purposes to determine the factors that influence the infant diaper dermatitis and assess the relationship between these factors and the diaper dermatitis. The study design is an analytical observational with a cross sectional study design. Data retrieval using interview method on respondents use a structured questionnaire to obtain risk factors which are associated with the diaper dermatitis incidence. Bivariate analysis was used to examine the relationship between the diaper dermatitis incidence and contributing factors. The study result is 27 infants (36%) of 75 infants had diaper dermatitis. It was obtained p value ≤ 0.05 for solid food (fishes, p = 0,018) and diarrhea (p = 0,021). The value of p > 0.05 for the variables of age, sex, maternal education level, neighborhood, solid foods (cereals, eggs and fruits), frequency of diaper changes, frequency of bathing, and the use of protective skin cream. The conclusion is there is a correlation between diaper dermatitis and the solid food (fishes) and diarrhea.